2020
DOI: 10.1016/j.contraception.2020.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of choosing long-acting reversible contraceptive methods when provided free-of-charge – A prospective cohort study in Finland

Abstract: Objective: To identify factors associated with choosing long-acting reversible contraception (LARC) (intrauterine device or contraceptive implant), when provided free-of-charge. Study design: This register-based cohort study comprises all women living in the city of Vantaa in the Helsinki metropolitan area during 2013-2014, with information on LARC initiations retrieved from electronic health records. Since January 2013, women in Vantaa can receive their first LARC method free-ofcharge at public contraceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, if this were the case, it would even further support our results. Likewise, because more than 20% of women who receive free contraception opt for a LARC method such as the LNG-IUS or contraceptive implants, 21 the same bias may concern the analyses on the HC types.…”
Section: Discussionmentioning
confidence: 99%
“…However, if this were the case, it would even further support our results. Likewise, because more than 20% of women who receive free contraception opt for a LARC method such as the LNG-IUS or contraceptive implants, 21 the same bias may concern the analyses on the HC types.…”
Section: Discussionmentioning
confidence: 99%
“…This finding most likely reflects the high use of LARC methods among parous women. In fact, parous women were more likely to choose LARC methods than nulliparous women at the family planning clinics of Vantaa [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, women with a history of induced abortion were most likely to be aware of the services and had higher odds of service use across all age groups. Surprisingly, women with a history of induced abortion in Finland were found to have lower rates of hormonal contraceptive use [27], whereas, young women with a history of induced abortion were especially likely to choose LARC methods, which could explain the discrepancy in the studies [28].…”
Section: Discussionmentioning
confidence: 99%
“…45 Poor accessibility disproportionally impacts adolescents and, in support of this concern, researchers have found that the uptake of LARC methods (including post-abortion) increases when financial barriers are removed. [46][47][48] However, researchers are concurrently attempting to understand adolescent decision-making and document the practices of healthcare professionals in the context of LARC provision, particularly to "high-risk" groups such as adolescents. 49 In a preliminary search of the literature we identified a relative lack of research on acceptability and personcentered outcomes despite increasing emphasis on IPP/IPA LARC.…”
Section: Introductionmentioning
confidence: 99%
“…As LARC have similarly high rates of continuation across postpartum and nulliparous adolescents, 44 IPP provision of LARC is perceived by researchers, clinicians and advocates as being an accepted or preferred method to adolescent mothers 45 . Poor accessibility disproportionally impacts adolescents and, in support of this concern, researchers have found that the uptake of LARC methods (including post‐abortion) increases when financial barriers are removed 46‐48 . However, researchers are concurrently attempting to understand adolescent decision‐making and document the practices of healthcare professionals in the context of LARC provision, particularly to “high‐risk” groups such as adolescents 49 .…”
Section: Introductionmentioning
confidence: 99%